Museum virtual sebagai media pembelajaran sejarah pada program Kampus Mengajar 2 di SDI Azzahro Tangerang - Gery Erlangga; Amajida Triska Meilia; Nurul Hidayah; Jaja Miharja (Historiography: Journal of Indonesian History and Education, 2022)
This research discusses the topic of the role of technology-based learning media such as virtual museums in supporting the history learning process in schools. The position of history learning that has a central role in directing students to always be a superior generation, teachers should be able to create a learning process that is no longer focused on textbooks alone, but can present learning contextually with the help of alternative learning media that have innovative values such as virtual museums because they can foster students' interest in learning history. Therefore, the purpose of this study is to explain descriptively related to the use of virtual museums as an alternative learning medium to introduce history to SDI Azzahro students. This research uses a descriptive qualitative approach with a data collection process using observation and documentation techniques. The results of this study show that the use of virtual museums as a learning medium in history teaching and learning activities at SDI Azzahro has a positive impact as evidenced by the response of students to be more enthusiastic in learning history and dare to convey their understanding of the historical material they have studied in front of their friends.Penelitian ini membahas topik tentang peran media pembelajaran berbasis teknologi seperti museum virtual dalam memunjang proses pembelajaran sejarah di sekolah. Posisi pembelajaran sejarah yang memiliki peran sentral dalam mengarahkan peserta didik untuk senantiasa menjadi generasi unggul, sudah seharusnya guru dapat menciptakan proses pembelajaran yang tidak lagi terfokus pada buku teks saja, namun dapat menghadirkan pembelajaran secara kontekstual dengan bantuan media pembelajaran alternatif yang memiliki nilai inovatif seperti museum virtual karena dapat menumbuhkan daya minat peserta didik dalam belajar sejarah. Oleh karena itu, tujuan dari penelitian ini adalah untuk memaparkan secara deskriptif terkait dengan penggunaan museum virtual sebagai media pembelajaran alternatif untuk mengenalkan sejarah kepada peserta didik SDI Azzahro. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan proses pengambilan data menggunakan teknik observasi dan dokumentasi. Hasil penelitian ini menunjukan bahwa penggunaan museum virtual sebagai media pembelajaran dalam kegiatan belajar mengajar sejarah di SDI Azzahro memberikan dampak yang positif yang dibuktikan dengan respon peserta didik menjadi lebih semangat dalam belajar sejarah dan berani dalam menyampaikan kembali pemahamannya akan materi sejarah yang telah dipelajarinya depan teman-temannya.